2010
DOI: 10.1111/j.1365-294x.2010.04627.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of a recent climate change-driven range extension

Abstract: The life-history strategies of some species make them strong candidates for rapid exploitation of novel habitat under new climate regimes. Some early-responding species may be considered invasive, and negatively impact on 'naïve' ecosystems. The barrens-forming sea urchin Centrostephanus rodgersii is one such species, having a high dispersal capability and a high-latitude range margin limited only by a developmental temperature threshold. Within this species' range in eastern Australian waters, sea temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 66 publications
4
71
1
Order By: Relevance
“…This way, the effects of climate-induced range expansion on the genetic diversity of the edge populations can be minor. Although a decrease in allelic richness has been detected in edge populations in two studies (Watts et al, 2010;Garroway et al, 2011), all previous studies that have investigated genetic patterns of recent climate-induced range expansion also conclude that expansion occurred in a continuous wave of expansion with extensive gene flow (Watts et al, 2010;Dawson et al, 2010;Banks et al, 2010;Garroway et al, 2011;Buckley et al, 2012). In addition, the bottleneck analysis did not reveal a clear pattern of edge populations undergoing bottlenecks; instead we found evidence for a bottleneck in the recent past in two edge populations and one core population.…”
Section: Discussioncontrasting
confidence: 36%
See 1 more Smart Citation
“…This way, the effects of climate-induced range expansion on the genetic diversity of the edge populations can be minor. Although a decrease in allelic richness has been detected in edge populations in two studies (Watts et al, 2010;Garroway et al, 2011), all previous studies that have investigated genetic patterns of recent climate-induced range expansion also conclude that expansion occurred in a continuous wave of expansion with extensive gene flow (Watts et al, 2010;Dawson et al, 2010;Banks et al, 2010;Garroway et al, 2011;Buckley et al, 2012). In addition, the bottleneck analysis did not reveal a clear pattern of edge populations undergoing bottlenecks; instead we found evidence for a bottleneck in the recent past in two edge populations and one core population.…”
Section: Discussioncontrasting
confidence: 36%
“…Despite its relevance, only very recently the genetic consequences of natural, contemporary range expansions have started to receive attention (Watts et al, 2010;Banks et al, 2010;Garroway et al, 2011;Buckley et al, 2012). Results so far are equivocal.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, more attention has been paid to the consequences of natural, contemporary range expansions (Banks et al 2010;Garroway et al 2011;Swaegers et al 2013). These studies showed that the current range expansion may not only generate more independently replicated edge populations but also likely results in different population genetic patterns throughout the expansion front.…”
Section: Communicated By Pär Ingvarssonmentioning
confidence: 99%
“…Histories.-Invasive species have played a large role in changing global marine systems, in some cases drastically altering the biological communities of invaded areas (Blum et al 2007, Robinson et al 2007, Banks et al 2010, and are recognized as a pressing global concern (Sutherland et al 2010). The Indo-Pacific is no exception, with a number of non-indigenous species (NIS) recorded throughout the region.…”
Section: Detection Of Invasive Species and Reconstruction Of Invasionmentioning
confidence: 99%